The Impact of Cover Crop Biomass Introduction on the Dynamics of Nutrient Changes and Crop Productivity in Sandy-Clay Soils - Chenyi Li; Xiaohua Shi; Shuo Kong; Liguo Jia; Yonglin Qin; Jing Yu; Kun Liu; Mingshou Fan (Agronomy)
Sandy loam, characterized by inherently poor water retention capacity, necessitates the strategic utilization of fallow periods for soil conservation, with cover cropping serving as an effective ecological measure for nutrient retention. This study was conducted in the northern foothills of the Yinshan Mountains in Inner Mongolia, China, where the soil type is predominantly sandy loam. This study was conducted to elucidate the dynamic impacts of cover crops on soil nutrient profiles and their subsequent effects on following cash crops. Cover crops were cultivated during the fallow period and incorporated into the soil prior to spring tillage before planting the subsequent potato crop. Throughout the year following cover crop sowing, monthly measurements of soil organic matter (SOM) and nitrate nitrogen (<semantics><msubsup>NO3−</msubsup></semantics>-N) were performed to track temporal nutrient fluctuations. Concurrently, the biomass and yield of the subsequent potato crop were monitored to evaluate agronomic outcomes. The results indicate that the winter wheat treatment (WW) increased SOM by 2.54% after one year and elevated <semantics><msubsup>NO3−</msubsup></semantics>-N levels by 110.17% prior to potato planting. Subsequent potato cultivation exhibited yield enhancements of 2.51–3.83 t ha−1 relative to non-cover crop systems. Notably, 20% nitrogen reduction in basal fertilization did not compromise tuber yields while significantly improving nitrogen use efficiency by 8.7–12.3 percentage points and partial factor productivity of nitrogen by 14.6–18.9 kg kg−1, indicating optimized nitrogen stewardship under cover crop-mediated soil improvement regimes.